ANALYSIS OF THE IMPLEMENTATION OF THE INQUIRY-BASED LEARNING MODEL IN IMPROVING EXPLORATION SKILLS IN PRIMARY SCHOOLS - Tri Sutantina; Matsuri; Supianto (SOSIOEDUKASI, 2026)
This study was motivated by the fact that learning in primary schools still tends to be teacher-centred, so that students' exploration skills have not developed optimally. Previous studies have focused more on cognitive learning outcomes, while in-depth studies on the implementation of inquiry-based learning in improving students' exploration skills are still limited. This study aims to (1) analyse the implementation of the inquiry learning model in improving the exploration skills of fifth-grade students at SDN 03 Gedong, (2) analyse the obstacles encountered in implementing the inquiry learning model, and (3) analyse the solutions provided to overcome the obstacles in implementing the inquiry learning model. This study used a qualitative approach with a case study design. The research subjects included fifth-grade teachers and fifth-grade students. Data were collected through observation, in-depth interviews, and documentation studies. Data analysis was carried out through data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that (1) the implementation of the inquiry learning model can improve students' exploration skills, as indicated by an increase in curiosity, initiative in investigation, observation and experimentation skills, learning reflection, and independent learning, (2) Implementation constraints include time limitations, varying levels of student readiness, and teachers' experience in applying inquiry learning, (3) Solutions include structured learning planning, gradual guidance, and continuous learning reflection. These findings provide practical significance for primary school teachers in optimising student-centred learning and theoretical contributions to the development of inquiry learning studies that focus on students' exploration skills.